Maternal lead exposure induces sex-dependent cerebellar glial alterations and repetitive behaviors - Choi, Juwon; Kim, Yoo Sung; Kim, Mi-Hye; Kim, Hee Jung; Yoon, Bo-Eun (Frontiers in Cellular Neuroscience, 2022)
Lead (Pb) is one of the most prevalent heavy metals we encounter daily. Although there are many reports regarding their toxic effects on humans, the effects of exposure to low lead concentrations throughout the pregnancy period on the offspring are not fully elucidated yet. This study aimed to investigate the cellular mechanisms that occur in response to lead exposure. To this end, we administered lead-containing water to pregnant mice from the day of conception till delivery or till day 28 postnatally. Furthermore, we performed neurodevelopmental disorder-related behavior tests and RNA-sequencing analysis. We used both genders for all experiments because neurodevelopmental disorders usually show several sex-dependent differences. The results revealed increased levels of gliosis in the cerebella of lead-exposed pups compared to those in littermates belonging to the control group. Additionally, we observed altered behaviors of male mice in the autism spectrum disorder-related tests. RNA-sequencing results revealed changes in gamma-aminobutyric acid (GABA) signaling in the lead-exposed mouse model. Specifically, the lead-exposed male mice showed decreased monoamine oxidase B and increased levels of diamine oxidase enzyme, which is related to the synthesis of GABA in astrocytes. These findings demonstrate sex-dependent basal developmental changes in glial cells and an increased prevalence of autistic-like behaviors in the young pups of mothers exposed to lead during pregnancy.